Implementasi Pembelajaran Daring dalam Menghadapi Pandemi Covid-19 untuk Menjamin Hak Konstitusi Warga Negara Indonesia: Implementation of Online Learning in Facing the Covid-19 Pandemic to Guarantee the Constitutional Rights of Indonesian Citizens - Widiastuti, Anita Indah (Fakultas Hukum Universitas Negeri Semarang, 2021)
The emergence of the Covid-19 virus has certainly taken the whole world by storm. The Covid-19 virus first entered Indonesia in March 2020. With the Covid-19 virus, it certainly resulted in significant changes to all aspects of life, one of which was in the education aspect. Basically, education is the constitutional right of every Indonesian citizen as explained in Article 31 of the 1945 Constitution of the Republic of Indonesia which states that every citizen has the right to education, and every citizen is obliged to attend basic education and the government is obliged to finance it. Besides that, education is also basically a part of human rights, as stated in Article 28C Paragraph (1) and Article 28E Paragraph (1) of the 1945 Constitution of the Republic of Indonesia During the COVID-19 pandemic, the Indonesian government has taken various ways as one of the optimizing learning in Indonesia during this covid-19 pandemic. With the implementation of distance or online learning in Indonesia, it is one of the government's alternatives to continue to carry out learning activities during the pandemic. Online learning in Indonesia is also of course by utilizing advances in information and communication technology in the era of the industrial revolution 4.0. However, with the existence of online learning activities, this will certainly lead to new problems in its implementation. During online learning, of course, there will be positive and negative impacts in it. The purpose of this paper is to provide analysis as well as criticism and suggestions to the Indonesian government while implementing online learning during this covid-19 pandemic. The research method used in writing or research is by using doctrinal research methods, which are legal research conducted by conducting research on the study of library materials or secondary data on legal principles that occur, as well as by conducting research on certain case studies using descriptive analysis writing method.